Sequence- and structure-specific determinants in the interaction between the RNA encapsidation signal and reverse transcriptase of avian hepatitis B viruses. - Beck, J (1997)
Hepatitis B viruses (HBVs) replicate by reverse transcription of an RNA intermediate. Packaging of this RNA pregenome into nucleocapsids and replication initiation depend crucially on the interaction of the reverse transcriptase, P protein, with the cis-acting, 5' end-proximal encapsidation signal epsilon. The overall secondary structure is similar in all of the hepadnaviral epsilon signals, with a lower and an upper stem, separated by a bulge, and an apical loop. However, while epsilon is almost perfectly conserved in all mammalian viruses, the epsilon signals of duck HBV (DHBV) and heron HBV (D epsilon and H epsilon, respectively) differ substantially in their upper stem regions, both in primary sequence and in secondary structure; nonetheless, H epsilon interacts productively with DHBV P protein, as shown by its ability to stimulate priming, i.e., the covalent attachment of a deoxynucleoside monophosphate to the protein. In this study, we extensively mutated the variable and the conserved positions in the upper stem of D epsilon and correlated the functional activities of the variant RNAs in a priming assay with secondary structure and physical P protein binding. These data revealed a proper overall structure, with the bulge and certain key residues, e.g., in the loop, being important constraints in protein binding. Many mutations at the evolutionarily variable positions complied with these criteria and yielded priming-competent RNAs. However, most mutants at the conserved positions outside the loop were defective in priming even though they had epsilon-like structures and bound to P protein; conversely, one point mutant in the loop with an apical structure different from those of D epsilon and H epsilon was priming competent. These results suggest that P protein binding can induce differently structured epsilon RNAs to adopt a new, common conformation, and they support an induced-fit model of the epsilon-P interaction in which both components undergo extensive structural alterations during formation of a priming-competent ribonucleoprotein complex.